ENVIRONMENTAL MANAGEMENT IN THE COLLECTION OF SPECIAL WASTE - Silva, Vanessa Almeida da; Santos, Maríndia Brachak dos; Scherer, Flavia Luciane (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study aimed to identify the strategies and practices related to environmental issues in a company responsible for the collection, transportation, treatment and disposal of special waste. To that end, we reviewed the state of art related to the theme of environmental management and policy. The research was characterized as a case study, involving the opinions and perceptions of the organization’s managers about the environmental policies adopted by the company. Due to its performance in the area of special waste, disposal of paying for hospital solid waste from health services organizations, the company has its own characteristics that give specifics, as it is responsible for giving the appropriate destination for each of the different types of special waste, as well as the working conditions of employees who are often exposed to disease-causing agents . The main results showed that despite the absence of an environmental policy formally established, there was a concern on the part of managers in the organization to implement an environmental program that demonstrates the social responsibility of the organization, emphasizing the importance of an image legitimized in society.